Factors influencing smoking behaviours among male adolescents in Kuantan district - Mohd Yassin, Rapeah; Yaacob, Munirah; Othman, Latifah; K, Faizah; S, Norsimah; M, Maryana; Saub, Roslan (University of Malaya, 2008)
ABSTRACT The aims of this study were to determine the prevalence and factors that influenced smoking behaviours among male adolescents in Kuantan, Pahang. A cross-sectional study was conducted among the form four male students in Kuantan District. Three hundred and twenty three students were randomly selected from eight secondaryn schools. A self-administered questionnaire was distributed to all the respondents. Almost half of the sample was smokers (45.8%) and half of them were Malays (53.1%). Students whose parents had lower level of occupation were more likely to smoke (58.8%). Among smokers, 34.5% of them smoked since primary school and a majority (91.7%) smoked 10 or less cigarettes per day. Half of them (53.4%) reported that they bought loose cigarettes and most of them used their school pocket money to purchase the cigarettes (81.7%). From the multivariate analysis, it was found that Non-Science Stream classes (OR=3.92, 95% CI= 2.10, 7.32), peers' smoking(OR=6.07, 95% CI= 2.32, 15.92), and attitude towards smoking (OR= 21.93, 95% CI= 9.71,49.51) were significantly associated with smoking habit. The prevalence of smoking among male adolescents was considerably high'in this population. It is recommended that antismoking activities in school be carried out regularly and should involve an active participation from the adolescents themselves since peers have great influence on smoking habits.